Low colonic absorption drugs: risks and opportunities in the development of oral extended release products. (1st February 2018) - Xu, Jin; Lin, Yiqing; Boulas, Pierre; Peterson, Matthew L.
ABSTRACT: Introduction : Currently numerous drugs have been observed with lower colonic absorption than small intestine absorption, which can significantly impact in vivo performance of their oral extended release (ER) products. Areas covered : We reviewed over 300 publications, patents, book chapters, and commercial reports of drug products from regulatory agencies for low colonic absorption (LCA) drugs and critical findings are discussed. The focuses of this article are (1) current findings on the causes of low colonic absorption to support early assessment of LCA candidates, and (2) current knowledge on successful ER strategies and technical platforms used for LCA drugs in commercial drug products to facilitate oral ER product development. Expert opinion : Colonic drug absorption is one of the critical considerations in successful development of oral ER products. The root causes of low colonic absorption in many LCA drugs are still unclear. It is recommended to evaluate colonic drug absorption of drug candidate at early stage of oral ER product development. After evaluation, the selection of a formulation platform to develop an oral ER product needs to be carefully considered for LCA drugs. Based on the current commercial oral ER formulation platforms for LCA drugs, compounds are first divided into five types (I-V) and different ER formulation approaches with higher success rate are recommended for each type.